Degradable tough epoxy resin containing cation-pi action and preparation method of degradable tough epoxy resin

By introducing ester-containing multi-arm thiols and ionic liquids containing unsaturated double bonds and cation-π-acting epoxy resins into the epoxy resin, a high-toughness and degradable epoxy resin system is constructed, which solves the strength of epoxy resins when improving toughness. The sacrifice problem achieves dynamic reversibility and rapid degradation of the material, and has good recycling performance.

CN119431247AActive Publication Date: 2025-02-14HARBIN INST OF TECH

Patent Information

Application Number
CN202411790494.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-14
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

When existing epoxy resins improve toughness, they often lead to the sacrifice of material strength, and the mechanical deformation of their crosslinking network is incompletely reversible, limiting the energy dissipation of the material and the mobility of the chain segments.

Method used

By introducing ester-containing multi-arm thiols and ionic liquids containing unsaturated double bonds and cation-π-acting cation-π into the epoxy resin, a high-toughness degradable epoxy resin system is constructed by the light-thermal dual curing process. Under the action of external forces, the system achieves the dynamic reversibility of the material through energy dissipation of the cation-π action site and the intermolecular hydrogen bonding of the ester group.

Benefits of technology

It achieves the toughness and energy dissipation ability of the epoxy resin without sacrificing mechanical strength, and achieves rapid degradation under amine/alkaline conditions, and has good recycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431247A_ABST
    Figure CN119431247A_ABST
Patent Text Reader

Abstract

The invention discloses degradable tough epoxy resin with a cation-pi effect and a preparation method of the degradable tough epoxy resin. The epoxy resin is composed of multi-arm mercaptan containing ester groups, ionic liquid containing unsaturated double bonds and with the cation-pi effect and epoxy resin. According to the present invention, the multi-arm mercaptan containing the ester group, the unsaturated double bond ionic liquid and the epoxy resin can be combined through the light-heat dual curing process to construct the high toughness degradable epoxy resin system, and the whole method is green, simple and easy to operate. The energy dissipation capacity of the epoxy resin containing the cation-pi action is remarkably improved when the epoxy resin is stimulated by the outside, and cation-pi action sites uniformly dispersed in a network play a key role in the balance of rigidity and toughness under repeated loading-unloading circulation. Besides, ester groups in the structure enable the synthesized epoxy resin to have excellent degradation performance, hydrogen atoms in imidazole and the ester groups can form intermolecular hydrogen bonds, the degradation process of the resin is accelerated, and rapid degradation under the amine / alkaline condition is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an epoxy resin and a preparation method thereof, in particular to an ester group-cation-π-acting degradable tough epoxy resin and a preparation method thereof. Background Art

[0002] There is a trade-off between the strength and toughness of most materials. Increasing their crosslinking density usually leads to embrittlement, especially in thermosetting materials. Epoxy resin, as one of the most commonly used thermosetting resins, has been widely used in various fields, such as aerospace, transportation and electronics. Generally, highly crosslinked epoxy resins have excellent properties such as high modulus, strength and heat resistance, but the three-dimensional crosslinked network structure after curing limits the slippage of the molecular chain, resulting in unfavorable consequences such as high brittleness and poor crack propagation resistance, and ultimately causing permanent damage such as material failure. In the past few decades, methods of improving the toughness of resins by incorporating elastomers, thermoplastics, interpenetrating networks, and adding nanofillers have been widely studied. However, in most cases, the introduction of flexible structures inevitably leads to the sacrifice of material strength. Therefore, how to achieve the improvement of its ductility without sacrificing mechanical strength still needs in-depth research.

[0003] In recent years, through the study of toughened materials in nature, it has been found that the source of their toughness is the reversible chemical bonds and multi-level structural composition in the molecules. Among them, non-covalent interactions are considered to be a promising method for dissipating energy because they do not require additional energy for the bond breaking-reorganization process. Among them, non-covalent interactions such as hydrogen bonds, metal coordination bonds and host-guest interactions are widely used in materials such as elastomers and hydrogels through structural design, and have made major breakthroughs in high-toughness materials, confirming that the sacrificial strategy provided by non-covalent interactions provides a practical solution for designing high-toughness polymers. It is worth noting that for materials with such characteristics, the mechanical deformation of the cross-linked network should be completely reversible under small strains. Therefore, when the external force is withdrawn, sufficient molecular mobility is required to ensure the function of the sacrificial effect, and a certain amount of covalent cross-linking is required between the chains to provide restoring force. Epoxy resin has a highly rigid benzene ring structure, and the poor energy dissipation and segment mobility caused by the rigid structure are likely to limit the implementation of this sacrificial strategy in epoxy resin. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a cation-π-containing degradable tough epoxy resin and a preparation method thereof. The present invention can combine multi-arm thiol containing ester groups and unsaturated double-bond ionic liquids with epoxy resins through a simple light-heat dual curing process to construct a degradable epoxy resin system with high toughness. The whole method is green, simple and easy to operate. The energy dissipation capacity of the epoxy resin containing cation-π effects is significantly improved when stimulated by external stimuli, and the cation-π action sites uniformly dispersed in the network play a key role in the balance of stiffness and toughness under repeated loading-unloading cycles. In addition, the ester group in the structure makes the synthesized epoxy resin have excellent degradation performance, and the hydrogen atoms in the imidazole can form intermolecular hydrogen bonds with the ester group, accelerate the degradation process of the resin, and realize rapid degradation under amine / alkaline conditions, wherein the aminolysis solution can be recycled to participate in the re-curing of the epoxy resin, and has huge economic and environmental advantages in the fields of recyclable thermosetting resins and their composite materials.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] An ionic liquid containing an unsaturated double bond and a cation-π interaction has the following molecular structure formula:

[0007]

[0008] In the formula, R is not limited to Cl - Br - ,I - Br 3- , BF 4- PF 6- 、FSI - TFSI - 、SbF6 - , TfS - OH - 、CO3 2- , HCO 3- 、FeCl 4- 、AlCl 4- 、ZnCl 2- , CuCl 2- 、SO-、SDd - SHd - PB 2- R1 is an ionic liquid that can form a cation-π effect, but is not limited to a benzene ring, hexafluorobenzene, etc.

[0009] A method for preparing the above-mentioned ionic liquid containing unsaturated double bonds and cation-π interactions is prepared according to the following reaction process:

[0010]

[0011] Step 1: dissolve the reactant with R1 group and N-vinyl imidazole in an appropriate amount of solvent 1, and stir at room temperature to 88° C. for 6 to 72 hours, wherein:

[0012] The structural formula of the reactant with R1 group is:

[0013]

[0014] The molar ratio of the reactant with R1 group to N-vinyl imidazole is 1.01 to 2:1;

[0015] The solvent 1 is not limited to one of acetonitrile, tetrahydrofuran, methanol, ethanol, dioxane, and dichloromethane;

[0016] Step 2: precipitate the reaction mixture in step 1 in solvent 2 and centrifuge, wherein:

[0017] The solvent 2 is not limited to one of ether, n-hexane, petroleum ether, and ethyl acetate;

[0018] The number of centrifugation is 3 to 5 times, each time for 3 to 10 minutes;

[0019] Step 3: Collect the product and dry it to constant weight under vacuum to obtain an ionic liquid containing an unsaturated double bond and a cation-π reaction.

[0020] A cationic-π-action-containing degradable toughened epoxy resin is composed of a multi-arm thiol containing an ester group, an ionic liquid containing an unsaturated double bond and a cationic-π action, and an epoxy resin, wherein:

[0021] The multi-arm thiol containing an ester group is not limited to pentaerythritol (thioglycolate), pentaerythritol tetrakis (3-mercaptopropionate), dipentaerythritol hexa (3-mercaptopropionate), trimethylolpropane tris (3-mercaptopropionate), bis (thioglycolate) glycol ester, etc., and the structure contains an ester group and the number of thiol groups is ≥ 2, and when used, it can be one or more, and the multi-arm thiol is not limited to three-arm, four-arm, six-arm, etc.;

[0022] The molar ratio of the epoxy group to the mercapto group is 1:1, and the molar ratio of the unsaturated double bond to the mercapto group is 0.1 to 1:1;

[0023] The epoxy resin is one or more of glycidyl ether, glycidyl ester, glycidyl amine, aliphatic epoxy resin, alicyclic epoxy resin, trifunctional epoxy resin, tetrafunctional epoxy resin, phenolic epoxy resin, o-cresol epoxy resin, and nitrogen-containing epoxy resin.

[0024] A method for preparing the above-mentioned cationic-π-containing degradable toughened epoxy resin, according to Figure 1The reaction scheme shown is prepared:

[0025] The specific steps are as follows:

[0026] A one-pot method is adopted to mix a photoinitiator, a multi-arm thiol containing an ester group, an ionic liquid containing an unsaturated double bond and a cation-π action with an epoxy resin, and a degradable tough epoxy resin containing a cation-π action is generated by light-heat dual curing crosslinking, wherein:

[0027] The photoinitiator includes one or more of free radical type, cationic type, anionic type and ring-opening metathesis polymerization photoinitiator, but is not limited to IHT-PI 910, 659, 907, MBF, TPO, IHT-PI 4265, IHT-PI 1000, IHT-PI 500, benzoin, benzoin dimethyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, benzophenone, 2,4-dihydroxybenzophenone, diaryl iodonium salt, triaryl iodonium salt, alkyl iodonium salt, isopropyl ferrocenium hexafluorophosphate, and the added amount is 0.1-3wt% of the mass of the thiol;

[0028] The first stage of the light-heat dual curing crosslinking is UV curing, the selected wavelength is 365nm, and the irradiation time is 5 to 60 minutes; after the first stage of curing is completed, it is transferred to an oven for the second stage of curing, the curing temperature is 25 to 200°C, and the curing time is 60 to 360 minutes.

[0029] A method for degrading the above-mentioned cation-π-containing degradable toughened epoxy resin comprises the following steps:

[0030] Add an alkaline solvent or amine that can immerse the resin to the cationic-π-acting degradable toughened epoxy resin, and heat and stir at 50 to 150° C. until it is completely degraded, wherein:

[0031] The amount of the alkaline solvent or amine is at least 0.8 times the mass of the cationic-π-containing degradable toughened epoxy resin;

[0032] The alkaline solution is not limited to one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate, sodium carbonate, potassium carbonate, cesium carbonate, sodium thiosulfate, ammonia water, ammonium bicarbonate, etc., and the concentration is 0.5-6 mol / L;

[0033] The amine is not limited to one or more of diethylenetriamine, triethylenetetramine, tetraethylenepentamine, ethylenediamine, butanediamine, hexamethylenediamine, meta-xylylenediamine and the like.

[0034] Compared with the prior art, the present invention has the following advantages:

[0035] 1. The present invention adopts a one-pot method to synthesize an epoxy resin system containing an ester group and a cationic-π effect. The whole process is simple, has a high yield, and a fast reaction rate. The dynamically reversible cationic-π effect cross-linking site can increase the energy dissipation of the resin system through the bond breaking-recombination process when subjected to external force.

[0036] 2. The resin obtained by the present invention after curing not only has excellent mechanical properties, but also has good application in degradation and recycling. The rich ester groups in the structure and the adjustable glass transition temperature enable the series of resins prepared by the present invention to achieve rapid degradation under non-harsh conditions. The degradation conditions are amine / alkaline conditions. The aminolysis solution can also be used in the re-curing process of the epoxy resin, which will not generate secondary pollution sources to the environment. It is an economically feasible industrial production route. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The figure is a flow chart for the preparation of cationic-π-containing biodegradable toughened epoxy resin. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0039] Example 1: Ionic Liquids Containing Unsaturated Double Bonds and Cationic-π Interactions

[0040] 14.8 g of benzyl chloride and 10 g of N-vinyl imidazole were dissolved in 30 mL of acetonitrile, stirred and heated for 12 hours. Subsequently, the reaction mixture was precipitated in ether solvent and centrifuged at 10,000 rpm for 3 times, each for 10 minutes. Finally, the yellow liquid ionic liquid I was collected and dried under vacuum to a constant weight with a yield of about 90%. The molecular structure is as follows:

[0041]

[0042] Example 2: Ionic Liquid II Containing Unsaturated Double Bonds Interacting with Cation-π

[0043] 45 g of 2,3,4,5,6-pentafluorobenzyl bromide and 19 g of N-vinyl imidazole were dissolved in 200 mL of acetonitrile, stirred and heated for 12 hours. Subsequently, the reaction mixture was precipitated in ether solvent and centrifuged at 10,000 rpm for 3 times, each for 10 minutes. Finally, the white solid ionic liquid II was collected and dried under vacuum to a constant weight with a yield of about 90%. The molecular structure is as follows:

[0044]

[0045] Example 3: High toughness degradable thermosetting resin 1

[0046] At room temperature, 10 g of epoxy resin E51, 1 wt% of photoinitiator 2,4-dihydroxybenzophenone, 10.5 g of pentaerythritol tetrakis (3-mercaptopropionate) and 4.6 g of ionic liquid I were mixed evenly, degassed in a vacuum oven, and further transferred to a PTFE mold pre-coated with a release agent. First, it was irradiated under a UV lamp with a wavelength of 365 nm for 15 min, and then heated in an oven at 75 ° C for 2 h to completely cure. After cooling to room temperature, a high-toughness biodegradable epoxy resin I was obtained, and its thermodynamic properties are shown in Table 1.

[0047] Table 1 Thermodynamic properties of epoxy resin I

[0048]

[0049]

[0050] Example 4: High toughness degradable thermosetting resin II

[0051] At room temperature, 10 g of epoxy resin E51, 1 wt% of photoinitiator 2,4-dihydroxybenzophenone, 7.3 g of trimethylolpropane tris(3-mercaptopropionate) and 5 g of ionic liquid I were mixed evenly, degassed in a vacuum oven, and further transferred to a PTFE mold pre-coated with a release agent. First, it was irradiated under an ultraviolet lamp with a wavelength of 365 nm for 15 min, and then heated in an oven at 100 ° C for 2 h to be completely cured. After cooling to room temperature, a high-toughness biodegradable epoxy resin I was obtained, and its thermodynamic properties are shown in Table 2.

[0052] Table 2 Thermodynamic properties of epoxy resin II

[0053] project performance Tensile strength(MPa) 15±2 Tensile modulus(GPa) 1.0±0.2 Tensile strain (%) 100±20 <![CDATA[T g (℃)]]> 60~70 <![CDATA[T d5% (℃)]]> 290~300

[0054] Example 5: High toughness degradable thermosetting resin III

[0055] At room temperature, 10 g of epoxy resin E51, 1 wt% of photoinitiator 2,4-dihydroxybenzophenone, 9.5 g of dipentaerythritol hexa(3-mercaptopropionate) and 5 g of ionic liquid I were mixed evenly, degassed in a vacuum oven, and further transferred to a PTFE mold pre-coated with a release agent. First, it was irradiated under a UV lamp with a wavelength of 365 nm for 15 min, and then heated in an oven at 75 ° C for 2 h to completely cure. After cooling to room temperature, a high-toughness biodegradable epoxy resin III was obtained, and its thermodynamic properties are shown in Table 3.

[0056] Table 3 Thermodynamic properties of epoxy resin III

[0057] project performance Tensile strength(MPa) 40±5 Tensile modulus(GPa) 2±0.2 Tensile strain (%) 25±5 <![CDATA[T g (℃)]]> 100~120 <![CDATA[T d5% (℃)]]> 320~350

[0058] Example 6: High toughness degradable thermosetting resin IV

[0059] At room temperature, 10 g of epoxy resin E51, 1 wt% of photoinitiator 2,4-dihydroxybenzophenone, 10.5 g of pentaerythritol tetrakis(3-mercaptopropionate) and 8 g of ionic liquid II were mixed evenly, degassed in a vacuum oven, and further transferred to a PTFE mold pre-coated with a release agent. First, it was irradiated under an ultraviolet lamp with a wavelength of 365 nm for 30 min, and then heated in an oven at 100°C for 2 h to be completely cured. After cooling to room temperature, a high-toughness biodegradable epoxy resin IV was obtained.

[0060] Example 7: Degradable Thermosetting Resin I

[0061] Add 1g of high-toughness degradable thermosetting resin I and 2g of diethylenetriamine into a 50mL glass bottle and stir at 100℃ for 2h to completely degrade to obtain a clear and transparent yellow solution with a certain viscosity. Use 1.1g of the yellow solution and 6.0g of epoxy resin E-51 for curing. The curing procedure is 24h at room temperature and 1h at 100℃. The mechanical property retention rate of the obtained degradable thermosetting resin I is 80% of that of the high-toughness degradable thermosetting resin I cured with diethylenetriamine.

[0062] Example 8: Degradable Thermosetting Resin II

[0063] Add 1g of high-toughness degradable thermosetting resin I and 2g of ethylenediamine into a 50mL glass bottle and stir at 100℃ for 2h to completely degrade and obtain a clear and transparent yellow solution with a certain viscosity. Use 0.5g of the yellow solution and 5.0g of epoxy resin E-51 for curing. The curing procedure is 24h at room temperature and 1h at 100℃. The mechanical property retention rate of the obtained degradable thermosetting resin II is 85% of that of the high-toughness degradable thermosetting resin I cured by ethylenediamine.

[0064] Example 9: Degradation and recovery of degradable thermosetting resin III

[0065] Add 1g of degradable thermosetting resin I and 2g of m-xylenediamine into a 50mL glass bottle and stir at 100℃ for 4h to completely degrade and obtain a clear and transparent yellow solution with a certain viscosity. Use 1.8g of the yellow solution and 5.6g of epoxy resin E-51 to cure at 80℃ for 6h. The mechanical property retention rate of the obtained degradable thermosetting resin III is 90% of that of the high-toughness degradable thermosetting resin I cured by m-xylenediamine.

[0066] Example 10: Degradable Thermosetting Resin IV

[0067] Add 1g of high-toughness biodegradable thermosetting resin I and 0.5mol / L NaOH solution into a 50mL glass bottle and stir at 100℃ for 6h. The solution can be completely degraded to obtain a clear and transparent orange-yellow solution.

[0068] Example 11: Degradable Thermosetting Resin V

[0069] Add 1g of high-toughness biodegradable thermosetting resin I and 1mol / L NaOH solution into a 50mL glass bottle and stir at 100℃ for 2h. It can be completely degraded to obtain a clear and transparent orange-yellow solution.

[0070] Example 12: Degradable Thermosetting Resin VI

[0071] Add 1g of high-toughness degradable thermosetting resin I and 1mol / L NaOH solution into a 50mL glass bottle and stir at room temperature for 7 days. It can be completely degraded to obtain a clear and transparent light yellow solution.

[0072] Example 13: Degradable Thermosetting Resin VII

[0073] Add 1g of high-toughness biodegradable thermosetting resin IV and 1mol / L NaOH solution into a 50mL glass bottle and stir at 100℃ for 2h. The solution will be completely degraded to obtain a clear and transparent yellow solution.

[0074] Example 14: Degradable Thermosetting Resin VIII

[0075] Add 1g of high-toughness biodegradable thermosetting resin IV and 2g of triethylenetetramine solution into a 50mL glass bottle and stir at 100°C for 4h to completely degrade and obtain a clear and transparent yellow solution.

Claims

1. An ionic liquid containing an unsaturated double bond and a cation-π interaction, characterized in that The ionic liquid has the following molecular structure formula: In the formula, R is Cl - Br - ,I - Br 3- , BF 4- PF 6- 、FSI - TFSI - 、SbF6 - , TfS - OH - 、CO3 2- , HCO 3- 、FeCl 4- 、AlCl 4- 、ZnCl 2- , CuCl 2- 、SO-、SDd - SHd - PB 2- One of them; R1 is an ionic liquid that can form a cation-π interaction.

2. The ionic liquid containing an unsaturated double bond and a cation-π interaction according to claim 1, characterized in that The R1 is one of a benzene ring and hexafluorobenzene.

3. A method for preparing an ionic liquid containing an unsaturated double bond and a cation-π interaction as claimed in any one of claims 1 to 2, characterized in that The method comprises the following steps: preparing according to the following reaction process: Step 1: dissolve the reactant with R1 group and N-vinyl imidazole in solvent 1, and stir at room temperature to 88° C. for 6 to 72 hours, wherein: The structural formula of the reactant with R1 group is: The molar ratio of the reactant with R1 group to N-vinyl imidazole is 1.01 to 2:1; Step 2, precipitating the reaction mixture in step 1 in solvent 2 and centrifuging; Step 3: Collect the product and dry it to constant weight under vacuum to obtain an ionic liquid containing an unsaturated double bond and a cation-π reaction.

4. The method for preparing an ionic liquid containing an unsaturated double bond and a cation-π reaction according to claim 3, characterized in that The solvent 1 is one of acetonitrile, tetrahydrofuran, methanol, ethanol, dioxane and dichloromethane; the solvent 2 is one of ether, n-hexane, petroleum ether and ethyl acetate; the number of centrifugation is 3 to 5 times, each time for 3 to 10 minutes.

5. A cationic-π-containing degradable toughened epoxy resin, characterized in that The epoxy resin is composed of a multi-arm thiol containing an ester group, an ionic liquid containing an unsaturated double bond and a cation-π reaction, and an epoxy resin, wherein: The ionic liquid containing unsaturated double bonds and cation-π has the following molecular structure formula: In the formula, R is Cl - Br - ,I - Br 3- , BF 4- PF 6- 、FSI - TFSI - 、SbF6 - , TfS - OH - 、CO3 2- , HCO 3- 、FeCl 4- 、AlCl 4- 、ZnCl 2- , CuCl 2- 、SO-、SDd - SHd - PB 2- One of the following; R1 is an ionic liquid that can form a cation-π interaction; The multi-arm thiol is one or more of pentaerythritol (thioglycolate), pentaerythritol tetrakis (3-mercaptopropionate), dipentaerythritol hexa (3-mercaptopropionate), trimethylolpropane tris (3-mercaptopropionate), and bis (thioglycolate) ethylene glycol ester; The molar ratio of the epoxy group to the mercapto group is 1:1, and the molar ratio of the unsaturated double bond to the mercapto group is 0.1 to 1:1; The epoxy resin is one or more of glycidyl ether, glycidyl ester, glycidyl amine, aliphatic epoxy resin, alicyclic epoxy resin, trifunctional epoxy resin, tetrafunctional epoxy resin, phenolic epoxy resin, o-cresol epoxy resin, and nitrogen-containing epoxy resin.

6. The cation-π-containing degradable toughened epoxy resin according to claim 5, characterized in that The R1 is one of a benzene ring and hexafluorobenzene.

7. A method for preparing a cationic-π-degradable toughened epoxy resin as claimed in any one of claims 5 to 6, characterized in that The method comprises the following steps: A one-pot method is adopted to mix a photoinitiator, a multi-arm thiol containing an ester group, an ionic liquid containing an unsaturated double bond and a cation-π action with an epoxy resin, and a degradable tough epoxy resin containing a cation-π action is generated by light-heat dual curing crosslinking, wherein: The first stage of the light-heat dual curing crosslinking is UV curing, the selected wavelength is 365nm, and the irradiation time is 5 to 60 minutes; after the first stage of curing is completed, it is transferred to an oven for the second stage of curing, the curing temperature is 25 to 200°C, and the curing time is 60 to 360 minutes.

8. The method for preparing a cationic-π-containing degradable toughened epoxy resin according to claim 7, characterized in that The photoinitiator is one or more of free radical type, cationic type, anionic type and ring-opening metathesis polymerization photoinitiator, and the added amount is 0.1-3wt% of the mass of the thiol.

9. A method for degrading a toughened epoxy resin containing a cation-π action as claimed in any one of claims 5 to 6, characterized in that The method comprises the following steps: An alkaline solvent or amine capable of immersing the resin is added to the cationic-π-acting degradable toughened epoxy resin, and the resin is heated and stirred at 50-150° C. until the resin is completely degraded.

10. The method for degrading a toughened epoxy resin containing a cation-π action according to claim 9, characterized in that The amount of the alkaline solvent or amine is at least 0.8 times the mass of the cationic-π-containing degradable toughened epoxy resin; the alkaline solution is not limited to one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate, sodium carbonate, potassium carbonate, cesium carbonate, sodium thiosulfate, ammonia water, and ammonium bicarbonate, and the concentration is 0.5-6 mol / L; the amine is not limited to one or more of diethylenetriamine, triethylenetetramine, tetraethylenepentamine, ethylenediamine, butanediamine, hexamethylenediamine, and meta-xylylenediamine.

Citation Information

Patent Citations

  • Underwater viscous and tough conductive hydrogel with supramolecular interaction and preparation method of underwater viscous and tough conductive hydrogel

    CN117304512A

  • Suspended emulsion resistance reducing agent for fracturing fluid and preparation method of suspended emulsion resistance reducing agent

    CN117430745A

Cited By

  • Degradable epoxy resin composite material with adjustable curing speed as well as preparation method and mild total recycling method thereof

    CN120118480A

  • Strong-service degradable epoxy resin insulating material and preparation method thereof

    CN120623127A

  • Strong service, degradable epoxy resin insulating material and preparation method thereof

    CN120623127B